Improving awareness of corneal donation: audit of practice and intervention in two clinical settings. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Schofield, Guy; Patel, Rina
Abstract : Background: Two audits were undertaken evaluating current practice relating to corneal donation in Kingston General Hospital (KGH) and Princess Alice Hospice, Esher (PAH). Current guidance recommends 100% identification of potential donors and a 100% rate of referral. A secondary aim assessed potential missed donors. Method: Fourty-one patients were identified at KGH, 38 at PAH. The KGH data comprised two sets of audit data from a complete audit cycle. Eligibility for donation was ascertained via Moorfield's Hospital Eye Bank. Medical records were examined determining eligibility for donation, written evidence of assessment for eligibility, discussion with patient or family and referral for donation. Results: In PAH 55% patients had no contraindications. No patient had documented evidence of eligibility, patient preference, family discussion or of referral. In KGH 54% had no contraindications. KGH data includes a re-audit designed to evaluate the impact a new formulation of LCP documentation and a teaching session had on practice. Preintervention there were no documented episodes. Postintervention data demonstrated three documented assessments for eligibility, and three documented discussions with families. Despite similar percentages of potential missed donors in the two centres, the reasons for exclusion in KGH were all related to underlying medical conditions, whereas in PAH 14/17 contraindications resulted from systemic steroid use. Conclusion: Many patients receiving end of life care in hospital or hospice settings could donate corneal tissue. Patient wishes were not sought in either centre. Specific assessment fields in LCP documentation and targeted education improve awareness of the issue among ward medical staff. Impending interventions at PAH include a proforma with a standard question concerning corneal donation and an information pack for staff to be given on induction. The use of adjuvant corticosteroids may prevent a patient from donating corneal tissue. If a patient wishes to donate this should influence decision making.